A Universal Organic Cathode for Ultrafast Lithium and Multivalent Metal Batteries - Fan, Xiulin; Wang, Fei; Ji, Xiao; Wang, Ruixing; Gao, Tao; Hou, Singyuk; Chen, Ji; Deng, Tao; Li, Xiaogang; Chen, Long; Luo, Chao; Wang, Luning; et al. (Angewandte Chemie (International ed.), 2018)
Low‐cost multivalent battery chemistries (Mg2+, Al3+) have been extensively investigated for large‐scale energy storage applications. However, their commercialization is plagued by the poor power density and cycle life of cathodes. A universal polyimides@CNT (PI@CNT) cathode is now presented that can reversibly store various cations with different valences (Li+, Mg2+, Al3+) at an extremely fast rate. The ion‐coordination charge storage mechanism of PI@CNT is systemically investigated. Full cells using PI@CNT cathodes and corresponding metal anodes exhibit long cycle life (>10000 cycles), fast kinetics (>20 C), and wide operating temperature range (−40 to 50 °C), making the low‐cost industrial polyimides universal cathodes for different multivalent metal batteries. The stable ion‐coordinated mechanism opens a new foundation for the development of high‐energy and high‐power multivalent batteries. A universal ultrafast organic cathode for multivalent batteries is reported. In contrast to slow solid‐state ion diffusion and phase transformation in inorganic materials with a stiff crystal structure, the soft structure of the PI@CNT composite with the ion‐coordination charge storage mechanism ensures ultrafast reaction kinetics, improving the traditional low power and poor cycle life of multivalent battery chemistries.